2014
DOI: 10.1155/2014/239861
|View full text |Cite
|
Sign up to set email alerts
|

A One-Class Classification-Based Control Chart Using the K-Means Data Description Algorithm

Abstract: This paper aims to enlarge the family of one-class classification-based control charts, referred to as OC-charts, and extend their applications. We propose a new OC-chart using the K-means data description (KMDD) algorithm, referred to as KM-chart. The proposed KM-chart gives the minimum closed spherical boundary around the in-control process data. It measures the distance between the center of KMDD-based sphere and the new incoming sample to be monitored. Any sample having a distance greater than the radius o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The results of this study show that the K chart is sensitive to small shifts in the mean vector, whereas the KNNDD chart is sensitive to moderate shifts in the mean vector. In addition, Gani and Limam 46 introduced a new chart using the KMDD algorithm and reported that their chart has a better performance in detecting small shifts of mean vector based on ARL than the K chart and KNNDD chart. To improve the performance of Kcharts, Maboudou-Tchao et al 47 used a one-class SVM technique based on the SVDD method for monitoring the mean vector based on Mahalanobis kernel.…”
Section: Kernel-based Learning Methodsmentioning
confidence: 99%
“…The results of this study show that the K chart is sensitive to small shifts in the mean vector, whereas the KNNDD chart is sensitive to moderate shifts in the mean vector. In addition, Gani and Limam 46 introduced a new chart using the KMDD algorithm and reported that their chart has a better performance in detecting small shifts of mean vector based on ARL than the K chart and KNNDD chart. To improve the performance of Kcharts, Maboudou-Tchao et al 47 used a one-class SVM technique based on the SVDD method for monitoring the mean vector based on Mahalanobis kernel.…”
Section: Kernel-based Learning Methodsmentioning
confidence: 99%
“…For example, a novel control chart for the OCC based on a k-nearest neighbor algorithm was introduced [6]. Another OCC-based control chart using the 𝐾𝐾-means data description (KMDD) algorithm, which is called the KM-chart, was proposed by Gani and Limam [23]. Moreover, the OC-SVM that adapts the SVM to the OCC was suggested [10].…”
Section: The Multi-class Classification Is Illustrated In (C)mentioning
confidence: 99%
“…This approach has been adopted by several authors and proven useful in real-world circumstances. [17][18][19][20] Finally, the OCC method over classical statistical methods is that no limit theorems are used to determine a control limit. This can reduce the effort required to comply with the data dependency.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, the radius of the hypersphere is determined according to preassigned significance levels. This approach has been adopted by several authors and proven useful in real‐world circumstances 17–20 . Finally, the OCC method over classical statistical methods is that no limit theorems are used to determine a control limit.…”
Section: Introductionmentioning
confidence: 99%